SUPERVISI KLINIS DALAM PENGELOLAAN PEMBELAJARAN IPA SD GUGUS GAJAH MADA KABUPATEN KLATEN - MULYADI, MULYADI (2011)
The aims of the research are: 1) to descript clinical supervision in natural sciences management at elementary school at group of Gajah Mada Klaten Distric to make planning of learning implementaton, 2) to descript clinical supervision in natural sciences management at elementary school at group of Gajah Mada Klaten Distric to implementation learning process, 3) to descript clinical supervison in natural sciences management at elementary school at group of Gajah Mada Klaten Distric to carry out evaluation of the natural sciences learning. This is a qualitative research within to get at six of elementary school at group of Gajah Mada, Klaten Disctric. The strategic in this research is etnograpic. Data collecting method is used depth interview, participan observation, and documentation. Data analysis technique in this research is used descriptive technique, trough reduction data procedure, data presentation, and taking conclusion or verification. Data verification used triangulation technique by source of triangulation technique, technique of triangulation, and time of triangulation. The result of the research are: 1) the implementation of clinical supervision in natural sciences management at elementary school at group of Gajah Mada Klaten Distric is increasing teacher's abilty to make planning of learning implementation, 2) the implementation of clinical supervision in natural sciences management at elementary school at group of Gajah Mada Klaten Distric to implementation learning process become advance, 3) the implementation of clinical supervision in natural sciences management at elementary school at group of Gajah Mada Klaten Distric to carry out evaluation of the natural sciences learning become advance too.